Effects of parenteral nutrition + best supportive nutritional care vs. best supportive nutritional care alone on quality of life in patients with pancreatic cancer: a secondary analysis of PANUSCO - Emanuel, Aline; Rosenberger, Friederike; Krampitz, Julia; Decker-Baumann, Christiane; Märten, Angela; Jäger, Dirk; Rötzer, Ingeborg (Supportive care in cancer, 2024)
Parenteral nutrition (PN) can be an effective treatment to improve the nutritional status of patients with pancreatic cancer, but the effects of PN on quality of life (QoL) are still understudied. Therefore, we aimed at investigating whether the best supportive nutritional care (BSNC) in combination with PN at home compared to BSNC alone changed QoL in patients with advanced pancreatic cancer undergoing chemotherapy over a period of 7 weeks.